Why Morality Will Continue to Flourish in a Secular Society After God: An Appreciation and a Short Criticism of the Late Engelhardt - Mori, Maurizio (Conatus - Journal of Philosophy, 2018)
The paper is mostly limited to an analysis of the main theses advanced by Engelhardt in his great book After God (2017), compared with those elaborated in the first edition of The Foundation of Bioethics (1986). The first part is devoted to a summary of Engelhardt’s proposals, and two of them are criticized in the second part. In particular, Engelhardt is doubtful that a morality after God is possible, while I argue that it is going to be produced and possibly will be more adequate than traditional morality. In the same line, Engelhardt holds that without God everything is meaningless, while I argue that meanings are instilled by humans in our projects, and that even in our forthcoming post-history age people will continue to have meaningful ethical actions.